White Man's Burden - Nakano, Desmond; Travolta, John.; Harry Belafonte; Kelly Lynch; Margaret Avery; Tom Bower; Andrew Lawrence; Bumper Robinson; Tom Wright; Sheryl Lee Ralph; Judith Drake; Robert Gossett; et al. (France A Band Apart, 1995)
The story takes place in alternative America where the blacks are members of social elite, and whites are inhabitants of inner city ghettos. Louis Pinnock is a white worker in a chocolate factory, loving husband and father of two children. While delivering a package for black CEO Thaddeus Thomas, he is mistaken for a voyeur and, as a result, loses his job, gets beaten by black cops and his family gets evicted from their home. Desperate Pinnock takes a gun and kidnaps Thomas, demanding justice.
Two men at odds in a world turned upside down.
Languages: English, Turkish Subtitle: Turkish
Keywords: Drama